Nutritional determination and comprehensive evaluation of different types of Huanghua low-salt shrimp sauce - ZHU Hongzhi, LI Yanguo, HE Xuejuan, LI Qiannan, TANG Wen (Zhongguo niangzao)
In this study, three kinds of low-salt shrimp sauce (low-salt dried peeled shrimp sauce, low-salt shrimp sauce and low-salt Penaeus orientalis sauce) were prepared, and their nutritional components were determined. At the same time, the three kinds of low-salt shrimp sauce were comprehensively evaluated by index of nutritional quality (INQ), upper limit of safe intake of nutrients (UL), amino acid score (AAS), atherogenic index (AI) and thrombogenic index (TI), etc. The results showed that the protein content of low-salt dried peeled shrimp sauce, low-salt shrimp sauce and low-salt P. orientalis sauce was 14.80 g/100 g, 14.90 g/100 g, 13.70 g/100 g, the amino acid scores were all higher than 97 points, the INQ value of minerals and vitamins were all higher than 1 (1.51-30.80), the risk index of vitamins and minerals was low (1.11%-13.33%), the AI value and TI value were 0.58, 0.35, 0.53 and 0.07, 0.16, 0.06, respectively, and the ratio of n-6 unsaturated fatty acids to n-3 unsaturated fatty acids (n-6PUFA/n-3PUFA) was 0.12, 0.98 and 0.16, respectively. Therefore, three kinds of low-salt shrimp sauce were low-energy, high nutrient foods, which had a lower risk on cardiovascular disease.